2010
DOI: 10.1002/eqe.1045
|View full text |Cite
|
Sign up to set email alerts
|

Shaking‐table tests of a full‐scale single‐story masonry veneer wood‐frame structure

Abstract: This paper presents the findings of shaking-table experiments conducted to examine the seismic performance of a full-scale, one-story, wood-framed structure with masonry veneer. The structure was designed and constructed in accordance with current U.S. code provisions. The veneer was attached to the wood backing with two kinds of metal anchors, corrugated ties fastened with 8d nails and rigid ties fastened with #8 screws. The tests have shown that the use of nails to fasten veneer anchors to the wood studs is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Some experimental investigations had focused on the static in-plane and out-of-plane behavior of the brick masonry veneer systems [10,12,13,19,20]. Some of the works have also focused on the dynamic shaking table tests of both brick veneer elements [7,10,12,13,16,[21][22][23][24] or full-scale or reduced-scale buildings with attached brick veneer walls [10,12,19,21,[25][26][27][28][29].…”
Section: Experimental Setup and Main Resultsmentioning
confidence: 99%
“…Some experimental investigations had focused on the static in-plane and out-of-plane behavior of the brick masonry veneer systems [10,12,13,19,20]. Some of the works have also focused on the dynamic shaking table tests of both brick veneer elements [7,10,12,13,16,[21][22][23][24] or full-scale or reduced-scale buildings with attached brick veneer walls [10,12,19,21,[25][26][27][28][29].…”
Section: Experimental Setup and Main Resultsmentioning
confidence: 99%
“…Kasal et al [13] performed a series of dynamic experiments on two-story glue-laminated timber frames with fiber-reinforced joints to obtain connection characteristics. Okail et al [14] presented the findings of shakingtable experiments conducted to examine the seismic performance of a full-scale, one-story, wood-framed structure with masonry veneer. e full-scale timber frame walls were tested to study their performance under compression and the results indicated that the stud-to-stud connections offered better improvement of load carrying capacity for the specimens under compression [15].…”
Section: Introductionmentioning
confidence: 99%
“…The use of clay brick masonry as an anchored wall veneer was first seen in late eighteenth century England (Mendygral and Sumnicht 2011), and today makes up approximately 45% of new residential dwellings in New Zealand (Beattie and Thurston 2011). Clay brick, or similar masonry veneer systems, is favored for its durability and resistance to fire and moisture, as well as for aesthetic reasons (Okail et al 2011). However, observations made from previous earthquakes have highlighted that masonry veneer systems exhibit poor performance when subjected to lateral loads.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate performance of masonry veneer systems was observed in the M5.6 1989 Newcastle, Australia earthquake, with pull-out of the ties connecting the veneer to the timber wall framing commonly observed (Page 1991). The M6.7 1994 Northridge, California earthquake also resulted in considerable damage to older brick veneer systems, largely attributed to a combination of differential movement between the masonry veneer and the timber framing and the poor anchorage of ties connecting the masonry veneer to the timber wall framing (Okail et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation